The awareness of UiTM Cawangan Pahang students on legal rights and data protection in Social Networking Site (SNS): The case of facebook / Mohd Ikhsan Md Raus, Ikmal Hisham Md Tah and Saadiah Yahya - Md Raus, Mohd Ikhsan; Md Tah, Ikmal Hisham; Yahya, Saadiah (2012)
The growth of the internet has made online social networking popular among billions of individuals around the world. However, these people seem to forget that somehow they are revealing their personal information to people who are not in the circle of friends. Exposing real names, uploading pictures, revealing private information and updating their current status are some of the features provided by the SNS, namely Facebook. Furthermore, there is no awareness among the Malaysians who use Facebook especially about their rights and protections by the law. Despite the risks of using SNS, the Malaysian laws do not specifically address the legislation or rules to guide the usage of SNS but it is relevant to discuss under Malaysian Personal Data Protection Act 2010 and laws pertaining to privacy. These two laws are the main concern within this paper in order to look whether the students know the idea on data protection and privacy. Thus, a set of questionnaire has been distributed to a group of students randomly to measure their perceptions on the data visibility via Facebook and suggested the precaution that should be taken to prevent any unintended issues such as cybercrime, suicide, sexual harassment, identity theft, copyright infringement involving videos and pictures. The analysis findings revealed that 68.6% of respondents were aware of the risks occurring once they disclose their private information in Facebook and 69% of them were aware that they have the rights on the personal information provided under a law. Unfortunately, there are only 31% of respondents who were aware of the Personal Data Protection Act 2010 which was gazetted in June 2010. Through education and awareness, users will be more willingly and effectively utilize privacy and security settings available on SNS (Vinson, 2010).